Annotations on a Scandal: Desire, Transgression, and the Filmic Fantasy of Pedagogy. Issue 5 (October 2015) - Stillwaggon, James; Jelinek, David
ABSTRACT From Socrates to Jean Brodie, we have become accustomed to teachers serving as placeholders for transgressive and powerful desires in our cultural imaginary. Evidenced by recent scholarship on teachers in film, however, as well as by the 2006 film Notes on a Scandal, the way we ought to feel about teachers acting on their transgressive motivations, realizing the cultural fantasies that shadow desire and break from social norms, is less clear. In this article James Stillwaggon and David Jelinek frame the problematic erotics of school films in terms of the fantasy of the subject presumed to know and the transgressive bliss of jouissance. Stillwaggon and Jelinek analyze Notes on a Scandal as a breakdown and reversal of the tradition of school films to which it is indebted and work from it toward an understanding of the unrecognized and often conflicted cultural commitments that shape teaching.